Review on community food security and edible insect’s resources: biodiversity and policy implications for safeguarding human consumption. - Ayieko, Monica A. (Scitecpub, 2013)
The aim of this paper is to review the impact of climate change on food security with emphasis to alternative food resources such as edible insects in the Lake Victoria region. It goes further and outlines basic recommendations and policy issues for mitigation. There is increasing concerns that climate change is compromising achievement of the Millennium Development Goal activities. Climate change is affecting food security by influencing agricultural production, distribution and consumption pattern in many areas. The most affected nations are the developing countries such as Kenya whose efforts in poverty reduction have been reduced. Market forces and voluntary choices influence individual decisions about what food to eat and how to maintain good health under changing climate. Even though climate change indicators predict increase of land under crop production of third world, food production, distribution and consumption pattern of villagers remain evasive. Many African communities regularly eat edible insects. Climate change has seen such insects increase and the villagers are having a second look at entomophagy. However, the risks the villagers face is contamination by agrochemical pesticides. The government is thus called upon to oversee the wanton and indiscriminate use of the chemicals to safe guard the health of the villagers who practice entomophagy.
Keywords: Entomophagy; Edible insects; Policy; Environment; Food Security